Children who live in disadvantaged areas: a case study of the health and well-being perceptions and experiences of school-aged children and their families - HOLLYWOOD, ELEANOR (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2020)
Background: Recent times have witnessed the development of a new appreciation towards child health and well-being and consequently there has been an upsurge of research concerning various aspects of children's lives. Positive health in childhood sets the scene for good health in adulthood which is beneficial for all of society. There are however disparities in child health, and the social determinants of health such as the circumstances into which children are born, grow up and live in, are all influenced by economic, political and social forces, thus collectively shaping child health and well-being. The aim of the study presented in this thesis was to explore the health and well-being related perceptions and experiences of school-aged children and their families, who live in areas of urban disadvantage. Although much of the research to date concerning children's lives aims to better understand children's lives it remains that little is known about the lives of children who live in disadvantaged areas. Methodology: Case study research was adopted to achieve the study objectives which encompassed the exploration of 'family' and 'health' with children and families from areas of urban disadvantage. The case in this research is a single case which is comprised of a unit of analysis (15 participating families) and sub-units of analysis (fieldnotes and archival records). Data collection consisted of face-to-face interviews with children, parents and grandparents, recording of study fieldnotes and the collection of archival data. Thematic analysis was employed to analyse the variety of data sources. Findings: Findings indicate that children view their personal family composition very differently to adults. Family support exists in various formats within families which contributes positively to child health and well-being. Children in the study demonstrated a holistic understanding of health and view the concepts of health and well-being interchangeably. Maternal grandparents occupy a special place in the life of the child who lives in an urban disadvantaged area. Parenting issues are exacerbated by financial constraints experienced by families. The study found that the greatest challenge for parents of children from areas of urban disadvantage is keeping their children safe from drugs and drug related activity. Children view their area in a mostly positive light however, adults have mixed feelings about the area where they live. Conclusion: Living in an area of urban disadvantage poses many challenges for the school-aged child and their family. This research provides a unique picture of the perceptions and experiences of the school-aged child and family who live in an area of urban disadvantage thus contributing to a greater understanding of these children's lives.
APPROVED
Keywords: Children; Well-being; Case study research; Disadvantage